2015
DOI: 10.1080/15384047.2015.1026510
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mTOR signaling pathways and related negative feedback loops for the treatment of acute myeloid leukemia

Abstract: An accumulating understanding of the complex pathogenesis of acute myeloid leukemia (AML) continues to lead to promising therapeutic approaches. Among the key aberrant intracellular signaling pathways involved in AML, the phosphatidylinositol 3-kinase/AKT/mammalian target of rapamycin (PI3K/AKT/mTOR) axis is of major interest. This axis modulates a wide array of critical cellular functions, including proliferation, metabolism, and survival. Pharmacologic inhibitors of components of this pathway have been devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 121 publications
0
27
0
Order By: Relevance
“…1,2 The selective targeting of these pathways could improve the outcome of the currently available, generally unsatisfactory, treatments for patients with AML. [3][4][5] The mitogen-activated protein kinase (MAPK) pathways regulate multiple cellular processes including leukemic cell proliferation, differentiation, and apoptosis. 1,6 Two key effectors of MAPK pathways are the MAPK interacting protein kinases 1 and 2 (Mnk1/2), which are activated downstream of MAP kinases and regulate the activation of eukaryotic translation initiation factor 4E (eIF4E).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The selective targeting of these pathways could improve the outcome of the currently available, generally unsatisfactory, treatments for patients with AML. [3][4][5] The mitogen-activated protein kinase (MAPK) pathways regulate multiple cellular processes including leukemic cell proliferation, differentiation, and apoptosis. 1,6 Two key effectors of MAPK pathways are the MAPK interacting protein kinases 1 and 2 (Mnk1/2), which are activated downstream of MAP kinases and regulate the activation of eukaryotic translation initiation factor 4E (eIF4E).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, autophagy pathway is negatively regulated by mTOR signaling [ 18 ]. Rapamycin inhibits mTOR pathway by directly binding to mTORC1 complex [ 32 ]. Our data demonstrated that the increased autophagy activity is mTOR-independent in imatinib-resistant CML cells ( Figure 2 E and Figure 3 B–D).…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 targeting by rapalogs could lead to unintended feedback amplification of the PI3K/AKT/mTOR pathway in AML, potentially subverting the clinical effect of targeting mTORC1 alone [ 4 , 5 ]. Several studies have demonstrated improved anti-leukemic effects in AML by targeting both mTORC1 and mTORC2 simultaneously using active site or catalytic inhibitors [ 34 ]. Interestingly, mTORC2 may be inhibited by high doses of rapamycin, leading to inactivation of AKT and ERK [ 6 ].…”
Section: Discussionmentioning
confidence: 99%